The Effect of Rice Husk Ash and Pineapple Leaf Fiber on Physical and Mechanical Properties of Concrete - Atikah, Nisrina; Frida, Erna; Nasution, Yulianti (Journal of Technomaterial Physics, 2023)
This study used the cast-in-situ method to make concrete based on rice husk ash and pineapple leaf fiber. Rice husk ash and pineapple leaf fiber were used as the cement substitutes with different variations: 0%, 2.5%, 5%, and 7.5%. Parameters examined in this study included density, porosity, water absorption, flexural strength, and compressive strength using a universal testing machine and Material Testing equipment, which were then analyzed morphologically using SEM-EDX. The result showed a density of  2.510 × 103 − 2.451 × 103 kg/m3, porosity of 7.64 – 5.73 %, water absorption of 0.296 % – 0.243 %, compressive strength of 23.66 – 16.45 MPa, flexural Strength of 33.3 – 25.3 MPa. The morphological analysis showed that the rice husk ash and pineapple leaf fiber addition was responsible for the concrete's porous structure in this study has a porous structure. The EDX analysis result exhibited a high carbon percentage.